2009
DOI: 10.1177/1362361308091649
|View full text |Cite
|
Sign up to set email alerts
|

Electrodermal reactivity to emotion processing in adults with autistic spectrum disorders

Abstract: Although alterations of emotion processing are recognized as a core component of autism, the level at which alterations occur is still debated. Discrepant results suggest that overt assessment of emotion processing is not appropriate. In this study, skin conductance response (SCR) was used to examine covert emotional processes. Both behavioural responses and SCRs of 16 adults with an autistic spectrum disorder (ASD) were compared to those of 16 typical matched adults. Participants had to judge emotional facial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
63
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 25 publications
8
63
1
1
Order By: Relevance
“…In a study comparing the EDA of children with ASD to children with sensory modulation disorder alone, children with ASD had atypical physiological arousal (tonic EDA), while children with SMD had atypical higher physiological reactivity (phasic EDA) across all sensory domains when compared to typically developing controls (Schoen et al, 2009). Consistent with this study, Hubert, Wicker, Monfardini, and Deruelle (2009) found that children with ASD had lower skin conductance response (phasic response to stimulus) than controls on an emotional judgement task. However, Chang and colleagues (2012) found an opposite pattern in children with autism when they examined tonic baseline and phasic response to controlled auditory stimuli.…”
Section: Eda As a Physiological Measure Of Sensory Modulation And Foosupporting
confidence: 72%
“…In a study comparing the EDA of children with ASD to children with sensory modulation disorder alone, children with ASD had atypical physiological arousal (tonic EDA), while children with SMD had atypical higher physiological reactivity (phasic EDA) across all sensory domains when compared to typically developing controls (Schoen et al, 2009). Consistent with this study, Hubert, Wicker, Monfardini, and Deruelle (2009) found that children with ASD had lower skin conductance response (phasic response to stimulus) than controls on an emotional judgement task. However, Chang and colleagues (2012) found an opposite pattern in children with autism when they examined tonic baseline and phasic response to controlled auditory stimuli.…”
Section: Eda As a Physiological Measure Of Sensory Modulation And Foosupporting
confidence: 72%
“…Results to date are mixed: Hubert et al (2009) recently reported lower skin conductance responses (SCR) in an adult ASD sample compared to controls, when judging emotions in faces. This was in spite of similar behavioral performance, suggesting different strategies to achieve the same outcome, perhaps due to altered autonomic response.…”
Section: Psychophysiological Measures Of Anxiety In Autismmentioning
confidence: 92%
“…Only two FER studies, to our knowledge, have used physiological measures of arousal. Hubert et al (2009), measuring skin conductance responses, found reduced responses to emotional faces in an adult ASD group, indicating a lack of autonomic arousal in this condition. In addition, Bal and colleagues (2010), measuring respiratory sinus arrhythmia and heart rate, found evidence of higher baseline levels of arousal in ASD children.…”
Section: Autonomic Correlates Of Fermentioning
confidence: 96%